Phyllodes Tumor of the Mamma. Case Report - Lidia Torres Aja; José Alberto Puerto Lorenzo; Ileana López Cuellar (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
The Phyllodes Tumor is an infrequent mammary fibroepithelial neoplasia, with an epithelial benign component and a mesenquimal component that can be benign or malignant; it only represents 0.3 to 0.4 % of all of the mammary tumours. The case of a 50 year old female sex patient with Phyllodes tumour of the mamma of benign nature is presented. For the infrequent of this disease, it is considered valuable to publish this case.